ANALYSIS OF THE PREPAREDNESS OF RSU HAJI MEDAN IN DISASTER MANAGEMENT - Oktavia, Ratih; Susilawati, Susilawati; Muhajirina, Dinda; Raspiyahni, Raspiyahni; Nasution, Ummi Kalsum; Ardila, Maisyah; Sahputra, Muhammad (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Disaster is defined as an event or series of events that endanger and disrupt people's lives and livelihoods, caused by natural, non-natural, or human factors. This research aims to analyze the preparedness of RSU Haji Medan in disaster management. The research method in this study is qualitative with research instruments in the form of interview guidelines and documentation, and secondary data collected from guidelines and official hospital documentation related to disaster preparedness. The results showed that Medan Hajj General Hospital has taken significant steps in disaster preparedness, with a clear structure and command system, as well as an organized disaster management team. Early warning systems have been implemented in the new building, although evaluation is needed in the old building. Infrastructure management shows good preparedness, with backup generators and an organized logistics system.